2000
DOI: 10.1103/physrevlett.85.2352
|View full text |Cite
|
Sign up to set email alerts
|

Observation of “Ghost” Islands and Surfactant Effect of Surface Gallium Atoms during GaN Growth by Molecular Beam Epitaxy

Abstract: We observe "ghost" islands formed on terraces during homoepitaxial nucleation of GaN. We attribute the ghost islands to intermediate nucleation states, which can be driven into "normal" islands by scanning tunneling microscopy. The formation of ghost islands is related to excess Ga atoms on the surface. The excess Ga also affect island number density: by increasing Ga coverage, the island density first decreases, reaching a minimum at about 1 monolayer (ML) Ga and then increases rapidly for coverages above 1 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…In order to isolate each of the Ga-N site exchanges, we first prepare the ''1 1'' surface by growing GaN(0001) film at 600 C by MBE, then deposit a fractional monolayer (ML) nitrogen atom at lower than growth temperature to freeze any intermediate structures formed after the first Ga-N site exchange, and finally convert these structures to their final state, i.e., GaN bilayer, by continued STM imaging. We find the first exchange results in N incorporation at the subsurface T 1 site between the top and second Ga layer of the ''1 1'' surface, forming ''ghost'' islands, similar to those reported in earlier studies [9,10]. The second exchange that converts these islands to that of bilayer height can be triggered by continued STM imaging, which involves electrons tunneling to or from localized states associated with the second layer Ga, which are induced by N incorporation.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…In order to isolate each of the Ga-N site exchanges, we first prepare the ''1 1'' surface by growing GaN(0001) film at 600 C by MBE, then deposit a fractional monolayer (ML) nitrogen atom at lower than growth temperature to freeze any intermediate structures formed after the first Ga-N site exchange, and finally convert these structures to their final state, i.e., GaN bilayer, by continued STM imaging. We find the first exchange results in N incorporation at the subsurface T 1 site between the top and second Ga layer of the ''1 1'' surface, forming ''ghost'' islands, similar to those reported in earlier studies [9,10]. The second exchange that converts these islands to that of bilayer height can be triggered by continued STM imaging, which involves electrons tunneling to or from localized states associated with the second layer Ga, which are induced by N incorporation.…”
supporting
confidence: 84%
“…These metal-rich surfaces can impact the epitaxial growth of nitrides favorably, with highest quality materials often grown under group-III-rich conditions, while N-rich growth yields films that are rough and faceted [7,8]. Though a full microscopic explanation of these observations is still missing, several aspects of the roles of the metal-rich surfaces during GaN epitaxy have emerged [9][10][11][12]. It was found that the excess Ga can serve as an autosurfactant during growth, modifying the growth kinetics from diffusion limited to that of exchange limited [9][10][11].…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…This coverage variation in the adsorption heat would be consistent with a nonconstant desorption barrier and pre-exponential factor described by Adelmann. 7 A previous independent observation of the existence of "Ga islands different states" on the GaN͑0001͒ surface comes from Zheng et al, 20 who using scanning tunneling microscopy demonstrated that there is a form of Ga islands that is converted to another form by voltage application, i.e., charge injection. Therefore, this work indicated that there is a change in phase of Ga islands involving charges.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5] GaN crystallizes in the stable wurtzite and metastable zinc-blende structure. The zinc-blende structure has a smaller band gap ͑by 0.2 eV͒ and lacks the built-in polarization-induced electrical fields in contrast to the wurtzite case.…”
Section: Introductionmentioning
confidence: 99%